Suicide vs medical assistance in dying (MAiD): A secondary qualitative analysis. Issue 12 (1st December 2020) - Wiebe, Ellen R.; Shaw, Jessica; Kelly, Michaela; Wright, Alysia
Abstract: This is a secondary analysis of three qualitative studies about MAiD in which researchers asked about the differences between suicide and MAiD. In all, researchers interviewed 52 Canadians; 7 were people who had requested MAiD and had been found ineligible, 6 were MAiD providers and 39 were socially and economically marginalized. The overwhelming response was that MAiD is better than suicide in the context of suffering at the end of life. Whereas these people perceived suicide as uncertain, difficult, and something that was usually done alone and without support, they thought MAiD was certain, painless, and more socially acceptable.